2012
DOI: 10.1007/s13160-012-0075-z
|View full text |Cite
|
Sign up to set email alerts
|

Computing knapsack solutions with cardinality robustness

Abstract: The weighted region problem is the problem of finding the weighted shortest path on a plane consisting of polygonal regions with different weights. For the case when the plane is tessellated by squares, we can solve the problem approximately by finding the shortest path on a grid graph defined by placing a vertex at the center of each grid. In this note, we show that the obtained path admits ( √ 2 + 1)approximation. This improves the previous result of 2 √ 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A variant of the knapsack problem with a similar notion of robustness was proposed by Kakimura et al [22]. In this problem a knapsack solution needs to be computed, such that, for every k, the value of the k most valuable items in the knapsack compares well with the optimum solution using k items, for every k. Kakimura et al [22] restrict themselves to polynomial time algorithms and show that under this restriction a bounded competitive ratio is possible only if the rank quotient of the knapsack system is bounded. In contrast, our results show that if we do not restrict the running time and if we only require our solution to contain a good packing with k items for every k, then we can be (1 + ϕ)-competitive using our generic algorithm, even for generalizations like Multi-Dimensional Knapsack.…”
Section: Theorem 2 For Every Cardinality Constrained Problem With a Mmentioning
confidence: 99%
“…A variant of the knapsack problem with a similar notion of robustness was proposed by Kakimura et al [22]. In this problem a knapsack solution needs to be computed, such that, for every k, the value of the k most valuable items in the knapsack compares well with the optimum solution using k items, for every k. Kakimura et al [22] restrict themselves to polynomial time algorithms and show that under this restriction a bounded competitive ratio is possible only if the rank quotient of the knapsack system is bounded. In contrast, our results show that if we do not restrict the running time and if we only require our solution to contain a good packing with k items for every k, then we can be (1 + ϕ)-competitive using our generic algorithm, even for generalizations like Multi-Dimensional Knapsack.…”
Section: Theorem 2 For Every Cardinality Constrained Problem With a Mmentioning
confidence: 99%
“…A variant of the knapsack problem with a similar notion of robustness was proposed by Kakimura et al [19]. In this problem a knapsack solution needs to be computed, such that, for every k, the value of the k most valuable items in the knapsack compares well with the optimum solution using k items, for every k. Kakimura et al [19] restrict themselves to polynomial time algorithms and show that under this restriction a bounded competitive ratio is possible only if the rank quotient of the knapsack system is bounded.…”
Section: Corollary 3 If There Is a Polynomial Time α-Approximation Al...mentioning
confidence: 99%
“…A variant of the knapsack problem with a similar notion of robustness was proposed by Kakimura et al [19]. In this problem a knapsack solution needs to be computed, such that, for every k, the value of the k most valuable items in the knapsack compares well with the optimum solution using k items, for every k. Kakimura et al [19] restrict themselves to polynomial time algorithms and show that under this restriction a bounded competitive ratio is possible only if the rank quotient of the knapsack system is bounded. In contrast, our results show that if we do not restrict the running time and if we only require our solution to contain a good packing with k items for every k, then we can be (1 + ϕ)-competitive using our generic algorithm, even for generalizations like Multi-Dimensional Knapsack.…”
Section: Corollary 3 If There Is a Polynomial Time α-Approximation Al...mentioning
confidence: 99%
“…A related knapsack variant with an uncertain cardinality bound has been studied recently in [14]. It has been shown that any knapsack instance I admits a ν(I)-robust solution, where ν(I) is the rank of the knapsack system corresponding to I [11], and it is N P-hard to decide if a given instance admits an improved or even optimal robustness factor [14]. On the positive side, there is an FPTAS that finds solutions with nearly optimal robustness factor [14].…”
Section: Related Workmentioning
confidence: 99%
“…As our work shows, it may still be possible to get better solutions by focusing on instancessensitive guarantees. It is worth noting that this approach has been pursued, albeit not in a systematic way, in other contexts such as low-distortion embeddings of metrics into geometric spaces, e.g., in [6], subset selection problems [14], and earliest arrival network flows [9]. We hope that our work stimulates further research on instance-sensitive worst-case guarantees for other combinatorial optimization problems.…”
Section: Introductionmentioning
confidence: 99%